Bargaining game based on psychological cost of electric vehicles and risk assessment of aggregators. Issue 8 (27th March 2023) - Li, Yonggang; Lin, Hui; Zhou, Yichen; Zheng, Haoyang; Zhen, Xinghao; Bian, Zhaoyuan; Yue, Ziyi; Yang, Yang; Peng, Yonglong; Li, Yabin
Abstract: As electric vehicles (EVs) begin to participate in the peak‐shaving auxiliary service market, the question of how price aggregators can maximize the peak‐shaving capacity provided by EVs and maximize their own profit has become a major problem. This paper proposes a bargaining game pricing method based on the psychological cost of EVs and the risk assessment of aggregators. First, the comprehensive psychological cost of EV users is obtained based on the impact of users' participation in peak shaving on the battery life of EVs and on users' original travel plans and time, and the impact of aggregator pricing on users' psychology. Then, based on users' psychological cost and the law of gravitation, the evaluation scheme for the peak‐shaving capacity of EVs is obtained. On the basis of conditional value at risk (CVaR), the mixed CVaR is obtained by considering the risk‐chasing behaviour of users. Based on the mixed CVaR, the risk assessment of aggregators' participation in the peak‐shaving auxiliary service market is carried out. According to the above information, the aggregator and EV groups are engaged in a bargaining game based on the peak‐shaving pricing problem, which is divided into complete information game and incomplete information game. Finally, the feasibility of the proposed method is verified by an example analysis which is run by the MATLAB R2019b. The method proposed in this paper provides aggregators with a complete peak‐shaving electricity pricing scheme, effectively improving the dispatching capacity of EVs. It is helpful to rationalize the pricing of aggregators and maximize their profits. EVs can also obtain satisfactory profits, attracting more EVs to participate in peak shaving, and reduce the pressure on power grid peak shaving. Abstract : As electric vehicles begin to participate in the peak regulating auxiliary service market, it has become a major problem that how can price aggregator maximize the peak shaving capacity provided by electric vehicles and maximize their own interests. This paper proposes a bargaining game pricing method based on the psychology cost of electric vehicles and the risk assessment of aggregator.